Tolerance and Moderation in the Formulation of A Global Islamic Calendar - Muhammad Qorib; Arwin Juli Rakhmadi (STAI Serdang Lubuk Pakam, 2023)
The Global Islamic Calendar is a new breakthrough in the modern era with the aim of uniting all Muslims in a unified and integrated time scheduling system. In this regard, this study aims to analyze the dynamics of the global calendar and solutions to minimize differences in views. The research method used is qualitative based on literature study. Data analysis was conducted using content analysis. The results of the study revealed that the idea of a global calendar was motivated by the frequent differences in dropping the days of worship, especially Ramadan, Shawwal, and Zulhijah, not on the same day, even the difference reached more than two days. The idea of the Global Islamic Calendar has been rejected by a number of parties with all the reasons and rebuttals that cause the dynamics and discourse about it to continue to emerge. Considering the sharp differences, a moderate and tolerant attitude is needed from all parties because this issue is a fiqh issue that is prone to differences of opinion. Moderation and tolerance are the keys to the realization of the Global Islamic Calendar. This research certainly has implications for the improvement of Islamic knowledge, and also as an effort to unite the ukhuwah of the people.